Visualization in a Knowledge Transfer Process - Janusz Opiła (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Visualization is not only an important part of experimental data analysis process but also an efficient tool for transfer of acquired knowledge in multiple areas including, but not restricted to, ICT, general scientific discussion, innovation, data mining, decision support systems as well as education and learning. Consequently search for new and perfection of present visualization techniques is a necessity. In the paper, there are discussed selected visualization designs, doable using OpenSource tools such as ScPovPlot3D library, graph-drawing program ,,graphviz" or charting application ,,gnuplot". Presented ideas are discussed using two examples. The first one is a theoretical tool for consumer sentiment analysis, forecasting and what-if analysis focused on tourism. The second one is usage of graphing utility “graphviz” for visual analysis and revealing of hidden organisational structures.
Keywords: C01; C15; C44; C51; C53; D81; D83; D87; D91; L22; L25; Z32; 330; Visualization; Knowledge Transfer; Simulation; Sentiment Forecasting; graphviz